2017
DOI: 10.4238/gmr16039776
|View full text |Cite
|
Sign up to set email alerts
|

Research Article Genetic divergence in elite castor bean lineages based on TRAP markers.

Abstract: ABSTRACT. Castor bean (Ricinus communis L.) is a tropical plant of great commercial interest and a potential source of biodiesel. The development of genetically improved cultivars with high amounts of oil in the seeds and low ricin toxicity is crucial to increase the productivity of this crop. The use of TRAP (target region amplification polymorphism) markers to develop elite lineages and study genetic divergence is fundamental to advance the genetic improvement of this species. The goal of this study was to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
2
6
0
Order By: Relevance
“…TRAP primers were efficient in the amplification of the genomic DNA of castor bean, corroborating the results obtained by Simões et al (2017).The high means and wide variation of SOC among the elite strains obtained in this study indicate genetic variability for the castor bean breeding program of NBIO-UFRB.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…TRAP primers were efficient in the amplification of the genomic DNA of castor bean, corroborating the results obtained by Simões et al (2017).The high means and wide variation of SOC among the elite strains obtained in this study indicate genetic variability for the castor bean breeding program of NBIO-UFRB.…”
Section: Resultssupporting
confidence: 87%
“…The number of polymorphic fragments generated per combination varied from 2 (Trap17 x Arb2) to 10 (Trap28 x Arb4), with an average of 5.2 (Table 5). Simões et al (2017), when using a greater number of combinations of TRAP primers (330), including those used in this study, identified a variation from 2 (TRAP5 + ARB1; TRAP5 + ARB3; TRAP6 + ARB3; TRAP14 + ARB3; TRAP17 + ARB4; TRAP20 + ARB2; TRAP30 + ARB1; TRAP30 + ARB2; TRAP34 + ARB3) to 15 (TRAP22 + ARB6), with an average of 1.22 loci per combination.The mean of 5.2 polymorphic fragments per combination of primers found in the present study was close to the values of 4.8 derived from 70 combinations in castor bean (Simões et al, 2017), higher than 3.04 derived from 27 combinations of TRAP markers in sugarcane (Mirajkar et al, 2017) and lower than 13.30 derived from 12 TRAP combinations also in sugarcane (Creste et al, 2010).…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Many molecular markers like SSR (Simple Sequence Repeats), SNP (Single Nucleotide Polymorphism), EST-SSR (Expressed Sequence Tag-Simple Sequence Repeat), AFLP (Amplified Fragment Length Polymorphism), SCOT (Start Codon Targeted Polymorphism), RAPD (Random Amplified Polymorphic DNA), ISSR (Inter-Simple Sequence Repeat) and TRAP ((Target Region Amplification Polymorphism) have been used in assessing the genetic diversity of castor [1726]. Nonetheless, irrespective of the marker systems used, the global analysis of the genetic diversity of castor germplasm shows the low levels of variability and a lack of geographically structured genetic population [1719, 23].…”
Section: Introductionmentioning
confidence: 99%
“…These markers are characterized by their simplicity, high yield, reproducibility, and can be sequenced [ 26 ]. TRAP marker systems are used to study genetic diversity in different crop species such as castor bean [ 27 ], guarana [ 28 ], lettuce [ 29 ], mango [ 30 ], salvia [ 31 ], sugarcane [ 32 , 33 ], sunflower [ 34 ], and wheat [ 35 ].…”
Section: Introductionmentioning
confidence: 99%